Intervening in complex agrifood systems: Assessing outcomes of a multistakeholder approach in central Mozambique - Falk, Thomas; Kee-Tui, Sabine Homann; Hauser, Michael; Sixpence, Claudio; Quembo, Carlos João (International Food Policy Research Institute, 2023)
Inclusive co-design of system innovations incorporates diverse perspectives and bodies of knowledge that can generate solutions that fit well in a local context and over time influence the socio-technical regime. In operationalizing system transformation-oriented co-design processes, research and development actors have experimented in recent decades with the role of multistakeholder approaches. A specific application of such approaches in the agrifood system context are Agricultural Innovation Platforms (AIPs). Despite the growing application of AIPs and similar approaches, documentation of AIP achievements and assessment of their outcomes beyond the lifetime of the program are rare. We present an approach for integrating the logic of outcome harvesting into the process of AIP facilitation. We also document the outcomes from an AIP approach implemented in a mixed crop-livestock farming system in central Mozambique, using a mixed-methods approach. Our results indicate likely changes in behavior and behavioral drivers associated with the AIP approach. We also share experiences on methodological challenges in assessing outcomes of AIP processes. We hope that our results increase development actors’ confidence in applying AIPs at a larger scale.